Drug Related Cheilitis Along with Developed Angular Cheilitis: Case Report: Keilitis Terkait Obat Kemudian Muncul Angular Keilitis : Laporan Kasus - Amatul Firdaus Ramadhan,; Anandina Irmagita Soegyanto,; Febrina Rahmayanti, (Dentika: Dental Journal, 2024)
Isotretinoin is used to treat severe acne, and despite the therapeutic benefits, it has many side effects, including cheilitis on lips. This case report reviewed the importance of assessing the medical and pharmacological histories during anamnesis in the management of drug-related and angular cheilitis. Case: A 22-year-old female patient presented with complaints of dry, cracked, bleeding, and pain on the upper and lower lips, which occurred 7 days ago. Previous similar complaints were reported, although not severe. The patient had habits of lip licking, low water intake, and an irregular menstrual cycle. There was a history of using Roaccutane (isotretinoin) for acne treatment. Extraoral examination showed dry, desquamated lips with crusts, while intraoral examination had no abnormalities. Case management: The patient was prescribed NaCl 0.9%, Vaseline album, and hydrocortisone cream 1% twice daily. However, during treatment, angular cheilitis developed, prompting the prescription of miconazole cream 2% twice daily. One month later, all of the patient’s complaints were successfully treated with no subjective issues. Proper history taking and examinations were fundamental to making the right decisions and definite treatment plans.